Some observations on the procedures for the determination of the liquid limit: an application on plio-pleistocenic clayey soils from umbria region (italy) - Dragoni, Walter; Prosperini, Nicoletta; Vinti, Giuseppe (Italian journal of engineering geology and environment, 2008)
The procedures most commonly used in the geotechnical practice to determine the LL are the Casagrande device and the cone penetrometer, other techniques being no longer in use or still being tested. The liquid limit value obtained by the application of the Casagrande device, compared to the cone penetrometer method, is strongly dependent on the experience, practice and manual skills of the operator, whereas the cone procedure is more rational and independent from the operator, and it is as simple and economic as Casagrande's cup method. This note is to contribute to the studies regarding the comparison between the two methods and gives a relationship, statistically significant, between liquid limits determined by the two procedures for a set of natural soils of Central Italy. Results indicate that the difference between the two procedures increases with the increasing of the liquid limit. Moreover, the results show, in same cases, a not negligible variation of the position of the tested soils into the Casagrande Chart, depending on the procedure used for the determination of the liquid limit; it is suggested that perhaps this problem is worth further analysis.